2021
DOI: 10.3390/environments8120132
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of P. aeruginosa in Water Intended for Human Consumption and in Swimming Pool Water

Abstract: Considering the fact that water is a basic need of every living being, it is important to ensure its safety. In this work, the data on the presence of the opportunistic pathogen P. aeruginosa in drinking water (n = 4171) as well as in pool water (n = 5059) in Primorje-Gorski Kotar County in Croatia in the five-year period (2016–2020) were analysed. In addition, the national criteria were compared with those of neighboring countries and worldwide. The proportion of P. aeruginosa-positive samples was similar for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This scenario analysis shows that even high concentrations of 1 × 10 4 MPN/100 mL within a period of 30 min exposure would not exceed the USEPA benchmark. This statement is consistent with prior research indicating that this bacterium present in aquatic environments does not pose a significant threat to the general public (Hardalo & Edberg, 1997;Vukić Lušić et al, 2021).…”
Section: Scenario Analysis For Different Bacterial Concentrationssupporting
confidence: 92%
See 1 more Smart Citation
“…This scenario analysis shows that even high concentrations of 1 × 10 4 MPN/100 mL within a period of 30 min exposure would not exceed the USEPA benchmark. This statement is consistent with prior research indicating that this bacterium present in aquatic environments does not pose a significant threat to the general public (Hardalo & Edberg, 1997;Vukić Lušić et al, 2021).…”
Section: Scenario Analysis For Different Bacterial Concentrationssupporting
confidence: 92%
“…Moreover, Vukić Lušić et al. (2021) suggested that due to the widespread prevalence of this bacterium, it may not pose a significant threat to the general public.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of the bacterium is responsible for off-flavours, pigmentation, slime and malodour production in meat and derived products (Stellato et al, 2017). Previous studies showed that drinking water contaminated with P. aeruginosa may cause foodborne infections (Wei et al, 2020;Vukić Lušić et al, 2021). Additionally, there is growing evidence implication of the P. aeruginosa in foodborne infections (Bricha et al, 2009;Nawaz & Bhattarai, 2015;Virupakshaiah & Hemalata, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of P. aeruginosa to adapt to the harsh condition and metabolic flexibility is proved by their evolution from mere bacteria into virulence bacteria such as PA14 and PA01 [34,35]. The virulence factor in bacteria in an environmental context focuses on P. aeruginosa in decreasing water quality by producing biofilm [36].…”
Section: Introductionmentioning
confidence: 99%